Timing of neonatal stoma closure: a survey of health professional perspectives and current practice. Issue 4 (19th August 2021) - Ducey, Jonathan; Kennedy, Ann M; Linsell, Louise; Woolfall, Kerry; Hall, Nigel J; Gale, Chris; Battersby, Cheryl; Penman, Gareth; Knight, Marian; Lansdale, Nick
Abstract : Optimal timing for neonatal stoma closure remains unclear. In this study, we aimed to establish current practice and illustrate multidisciplinary perspectives on timing of stoma closure using an online survey sent to all 27 UK neonatal surgical units, as part of a research programme to determine the feasibility of a clinical trial comparing 'early' and 'late' stoma closure. 166 responses from all 27 units demonstrated concordance of opinion in target time for closure (6 weeks most commonly stated across scenarios), although there was a high variability in practice. A sizeable proportion (41%) of respondents use weight, rather than time, to determine when to close a neonatal stoma. Thematic analysis of free text responses identified nine key themes influencing decision-making; most related to nutrition, growth and stoma complications. These data provide an overview of current practice that is critical to informing an acceptable trial design. Abstract : This survey reports the perspectives of 166 respondents from 27 UK neonatal surgical centres regarding timing of neonatal stoma closure